Pengujian Fungsional Sistem Absensi Sekolah Berbasis QR Code Menggunakan Standar ISO/IEC 29119 - Herdiansyah, Gilang; Gymnastiar, Alfarisi; Anwar, Chairul (Journal of Information Systems and Business Technology, 2025)
Particularly for activities like taking attendance, the use of information technology in education is becoming more and more prevalent. Conventional methods of monitoring attendance are regarded as inefficient because of the large amount of time they take and their vulnerability to mistakes. A QR Code-based attendance system has, therefore, been chosen to increase both efficiency and accuracy. This system needs to be tested before it is fully deployed to ensure that it satisfies user requirements and that all of its features operate as expected. In accordance with the ISO/IEC 29119 standards, this study aims to test the software of a QR Code-Based School Attendance System. The methodology employed is functional testing utilizing the black box testing technique. As per ISO/IEC 29119 standards, the testing phases include planning, creating test cases, running tests, and reporting results. The testing prioritizes the system's essential functions, including attendance report administration, QR code creation, QR code scanning, and user login. The results demonstrate that the majority of the system's features perform as planned and adhere to the acceptance standards set. In light of these findings, the QR Code–Based Attendance System is considered adequate for supporting attendance management in educational institutions.